Understanding the tumor microenvironment for personalized immunotherapy in early-onset head and neck squamous cell carcinoma - Shan, Yidan; He, Di; Yan, Fengguo; Huang, Weijia (Frontiers in Immunology, 2025)
Early-onset head and neck squamous cell carcinoma (HNSCC) has been increasingly observed in recent years, exhibiting distinct tumor behavior and a unique tumor microenvironment (TME) compared to older age groups. Studies suggest that early-onset HNSCC is associated with specific risk factors and prognostic outcomes, while the underlying mechanisms driving these age-related differences remain unclear. In this review, we systematically examined original studies involving young HNSCC patient samples, focusing on the characteristics of the TME and potential for personalized immunotherapy. While further evidence is needed, our findings indicate that the TME in early-onset HNSCC often exhibits higher aggressiveness and immune suppression. Consequently, tailored immunotherapy may offer a promising therapeutic strategy for this distinct patient population.